Future Physicians of Pakistan Towards National Health Priorities - Nighat Huda (Journal of Bahria University Medical and Dental College)
With the dawning of 2011, Pakistan medical education direction continues towards preparing graduates for functioning in tertiary care settings. Medical educators and institutions take greater pride in producing specialists and sub-specialists who achieve laurels in developed countries. While Pakistan’s failure to meet the Millennium Development Goals (MDGs) by 20151 suggest reorientation of physicians’ education and research towards improvement of health of individuals and population.